Reforming Agricultural Extension System in Nepal: What can we adopt from selected Agriculture Led Countries? - Timsina, Krishna Prasad; Subedi, Sanjiv; Pandey, Sunita; Devkota, Deepa; Aryal, Aabhash; Lamichhane, Jeevan (Journal of Nepal Agricultural Research Council, 2023)
This paper compares the existing Nepalese agricultural extension system with other selected agriculture-led countries to explore the needs and opportunities of introducing an innovative agricultural extension system in Nepal. A review of various documents including journals, reports, and policy papers was carried out. The status of financial and human resources in agricultural extension of Nepal was assessed from 753 municipalities and 7 provinces through survey interviews and, additionally, expert consultations were done with 15 key personnel working in the field of agricultural extension in Nepal. We examined the major changes in the agricultural extension made before and after the federalization in Nepal and examined institutional arrangements and activities for agricultural sector governance after federalization. Further, three cases were selected from selected agriculture-led countries based on the working modality of research and extension either solely or jointly or in hybrid mode. The study found insufficient human resources for agriculture sector governance especially in provinces and municipalities with 37.4% and 29% of vacant positions, respectively. The recruited agriculture technicians were mostly engaged in administrative management and handout distribution rather than agricultural technology transfer. Most technicians were freshly recruited without any on-the-job training. The paper discussed about the agriculture extension approaches, service mechanisms and structure across the countries, and its relevancy in Nepal. Irrespective of operational modality of research and extension, technological advancement and application of Information Communication Technology plays an important role for the effectiveness of the extension services.